2012
DOI: 10.1002/ajmg.b.32078
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review and meta‐analysis on the association between BDNF val66met and hippocampal volume—A genuine effect or a winners curse?

Abstract: Inconsistenties have been reported with regard to an association between val(66)met, a polymorphism on the BDNF gene, and hippocampal volume. We performed a systematic review and a meta-analysis to determine the magnitude and direction of this putative association and estimated the potential influence of demographic, clinical, and methodological characteristics of studies. Tests of publication bias and time-related trends were performed and statistical power of the included studies was calculated. The literatu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
69
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 95 publications
(79 citation statements)
references
References 59 publications
2
69
2
Order By: Relevance
“…In volumetric studies Met-carriers were found to have a hippocampal volume reduction in both healthy cohorts and psychiatric patients with schizophrenia, bipolar disorder, major depression and anxiety disorders (Pezewas et al 2004, Szeszko et al 2005, Bueller et al 2006, Frodl et al 2007, Chepenik et al 2009, Mueller et al 2013). These observations were confirmed in three meta-analytic reviews (Hajek et al 2012, Kambeitz et al 2012, Molendijk et al 2012. However, the most recent meta-analyses showed no association between Val66Met polymorphism and hippocampal volumes neither in healthy subjects nor clinical groups (Harrisberger et al 2014(Harrisberger et al , 2015.…”
Section: Introductionmentioning
confidence: 71%
“…In volumetric studies Met-carriers were found to have a hippocampal volume reduction in both healthy cohorts and psychiatric patients with schizophrenia, bipolar disorder, major depression and anxiety disorders (Pezewas et al 2004, Szeszko et al 2005, Bueller et al 2006, Frodl et al 2007, Chepenik et al 2009, Mueller et al 2013). These observations were confirmed in three meta-analytic reviews (Hajek et al 2012, Kambeitz et al 2012, Molendijk et al 2012. However, the most recent meta-analyses showed no association between Val66Met polymorphism and hippocampal volumes neither in healthy subjects nor clinical groups (Harrisberger et al 2014(Harrisberger et al , 2015.…”
Section: Introductionmentioning
confidence: 71%
“…43 Consistent with these individual reports, two meta-analyses (n = 399 and 3620, respectively) have confirmed that 66Met allele carriers have smaller bilateral hippocampi relative to 66Val homozygote controls. 44,45 However, these meta-analyses noted that the effect size of the 66Met allele on reduced hippocampal volume is relatively small 44 and that most studies suffer from underpowered samples. 45 This small effect size, when coupled with heterogeneous sampling and nuisance variability between studies, may explain why some studies have failed to report an effect of the Val66Met polymorphism on hippocampal structure and function.…”
Section: Human Neuroscience Of the Val66met Polymorphismmentioning
confidence: 99%
“…This could be related to other factors influencing brain physiology, including SSRI use, other genes (e.g. brain-derived neurotrophic factor [BDNF] (Molendijk et al, 2012), depressive state (Van Tol et al, 2011), or epigenetic influences ). However, previous studies by our group have shown no effects of SSRI use in this sample on brain morphology or activation during visuospatial or memory processing (Van Tol et al, 2012;Van Tol et al, 2011;Van Tol et al, 2010).…”
Section: Effect Of Ser704cys On the Brain Of Patients With An Affectimentioning
confidence: 99%